2014
DOI: 10.1002/ange.201308354
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Layered Ultrasmall Nanoplates of MoS2 Embedded in Carbon Nanofibers with Excellent Electrochemical Performance for Lithium and Sodium Storage

Abstract: The preparation and electrochemical storage behavior of MoS 2 nanodots-more precisely single-layered ultrasmall nanoplates-embedded in carbon nanowires has been studied. The preparation is achieved by an electrospinning process that can be easily scaled up. The rate performance and cycling stability of both lithium and sodium storage were found to be outstanding. The storage behavior is, moreover, highly exciting from a fundamental point of view, as the differences between the usual storage modes-insertion, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(98 citation statements)
references
References 40 publications
3
95
0
Order By: Relevance
“…1,2 Owing to its structural, electronic and electrochemical features, MoS 2 has been explored as the active material for various devices, including fieldeffect transistors, 3 light-emitting diodes, 4 biosensors, 5 lithium-ion batteries (LIBs) and hydrogen production. [6][7][8][9][10] MoS 2 shows a number of advantageous features when used as the anode of LIBs. First, MoS 2 has a theoretical specific capacity of 670 mAh g − 1 , which is almost double the capacity of graphite, the dominant anode material of current commercial LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Owing to its structural, electronic and electrochemical features, MoS 2 has been explored as the active material for various devices, including fieldeffect transistors, 3 light-emitting diodes, 4 biosensors, 5 lithium-ion batteries (LIBs) and hydrogen production. [6][7][8][9][10] MoS 2 shows a number of advantageous features when used as the anode of LIBs. First, MoS 2 has a theoretical specific capacity of 670 mAh g − 1 , which is almost double the capacity of graphite, the dominant anode material of current commercial LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Co-intercalation between graphite and diglymebased electrolyte could also achieve a relatively high capacity of B90 mA h g À 1 and long cycle life 15 . Recent findings have shown that the anode materials for SIBs based on alloy-type (for example, metallic and intermetallic materials [16][17][18][19] ) and conversion-type (for example, sulfides [20][21][22][23] ) exhibited high initial capacity, but suffered from poor cyclability most likely due to the large volume change and the sluggish kinetics. In addition, organic anode materials (for example, Na 2 C 8 H 4 O 4 ) and carboxylate-based materials have been investigated as anode materials for SIBs 24,25 , but the electronic conductivity and cyclability still remain the significant challenge.…”
mentioning
confidence: 99%
“…5d), P@AC@CNT-3 was tested at a current density of 0.1 C (158 mA h g −1 ) between 0.001 and 2 V (vs. Na + /Na). Compared with Li storage, both a lower voltage plateau and capacity were measured, ascribed to differences in the thermodynamics and kinetics of the lithiation and sodiation processes [9,45,46]. In addition, the SEI formation and irreversible Na insertion into AC@CNT also resulted in a decreased ICE value (87.3%) and a lower initial charge capacity of 1,487 mA h g −1 for P@AC@CNT-3 in NIBs (Table S4).…”
Section: Resultsmentioning
confidence: 99%